Building A Chat App Using Website-Based Cryptography - Abdul Robi Padri; Asro Asro (Publikasi Indonesia, 2026)
One of the social media that is popular today among the general public is the short message application. This research aims to develop a secure web-based chat application by applying cryptographic algorithms, especially Advanced Encryption Standard (AES) and Rivest–Shamir–Adleman (RSA), to maintain the confidentiality of messages. The increasing use of instant messaging apps raises serious concerns regarding data privacy and information security. This research uses a system development approach that includes the design, implementation, and testing stages. AES is used for symmetric encryption of the message body, while RSA is used for secure key exchange. System testing is conducted in a local network environment that involves multiple users to evaluate the system's functionality and performance. The results show that the application is able to encrypt and decrypt messages with high accuracy, supports multi-user communication, and maintains the confidentiality of messages during transmission. In addition, performance testing shows that the encryption and decryption processes run efficiently within acceptable time limits. The conclusion of this study shows that the integration of AES and RSA algorithms in web-based chat applications is effective in improving the security of digital communications. The implication of this study is that the hybrid cryptographic approach can be practically implemented on web-based communication systems to improve user data protection, as well as potentially applied to a variety of other digital communication platforms that require a high level of security.